2012
DOI: 10.1521/psyc.2012.75.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Can People Remain Engaged and Vigorous in the Face of Trauma? Palestinians in the West Bank and Gaza

Abstract: This is the first study of the relationship between being exposed to traumatic conditions and, yet, remaining engaged in life tasks and vigorous. A national random sample of adult residents (n= 1,196) of the Palestinian Authority were interviewed in person in a three-wave longitudinal study: (1) September–October 2007, (2) April–May 2008, and (3) October–November 2008. Using path modeling, we found that those who reported greater trauma exposure at time 1 reported modestly reduced engagement at time 3, mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 53 publications
(72 reference statements)
2
27
0
1
Order By: Relevance
“…A key question that remains as to whether resilience outcomes and resilience processes are the mirror opposite of pathological processes or outcomes, or whether they are in some ways qualitatively different. Experience from our research has found the same factors that predict psychopathology and ill-being in reverse predict resilience outcomes and to characterize resilience processes (Hobfoll, Johnson, Canetti, Palmieri, Hall, Lavi, & Galea, 2012). This supports the mirror image model.…”
Section: Remaining Key Issuesmentioning
confidence: 95%
“…A key question that remains as to whether resilience outcomes and resilience processes are the mirror opposite of pathological processes or outcomes, or whether they are in some ways qualitatively different. Experience from our research has found the same factors that predict psychopathology and ill-being in reverse predict resilience outcomes and to characterize resilience processes (Hobfoll, Johnson, Canetti, Palmieri, Hall, Lavi, & Galea, 2012). This supports the mirror image model.…”
Section: Remaining Key Issuesmentioning
confidence: 95%
“…A rich body of literature documents the impact of chronic conflict, violence, humiliation, and imprisonment on Palestinian social institutions, family function, personal coping mechanisms, and development of social support networks (see Khamis 1993;Punamäki et al 2002Punamäki et al , 2005Kanninen et al 2003;Giacaman et al 2004;Roy 2004;Peltonen et al 2010;Hobfall et al 2012 for examples). It should come as no surprise that levels of stress, anxiety, and trauma symptomology are elevated in Palestinian populations living in both West Bank and Gaza Strip communities who are exposed to armed conflict and violence (de Jong et al 2003;Giacaman et al 2007;Khamis 2008;Qouta et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Redundant and unclear items were deleted or reworded, and several items, such as prayer, were added. The Way of Coping that used in this study shortened to 44 items divided in 7 subscales as follow: Wish and avoidance thinking including the following items (3,11,19,21,34,39,42), planful problem solving including the following items (7,12,15,23,43,44), positive reappraisal including the following items (5,8,9,16,20,31,32,38,40), seeking social support including the following items (1,17,24,30,33), accepting responsibility including the following items (2, 10,18, 26, 41), self-control including the following items (6,13,14,22,28,35,37), escape avoidance including the following items (4,25,27,29,36). The validity of this scale was tested before in study by Folkman et al among community sample of people and showed their alphas independently as follow [19]; confronting coping (alpha=0.70); Distancing (alpha=0.61); self-controlling (alpha=0.70); seeking social support (alpha=0.76); accepting responsibility (alpha=0.66); escape and avoidance (alpha=0.72); planful problems solving (alpha=0.68); and positive reappraisal (alpha=0.79).…”
Section: Ways Of Copingmentioning
confidence: 99%
“…Palestinians have experienced, in addition to chronic stressors and other personal interpersonal traumas and poverty, years of intergroup violence in the Israeli-Palestinian conflict and resulting refugee status without a land or recognized national identity. Palestinians are also experiencing a civil war; Palestinian factions fight for the leadership of Palestinian people with very different visions of what they hope to accomplish and how they hope the Palestinian State will be governed [1].…”
Section: Introductionmentioning
confidence: 99%